Cascade Coupling of Ene‐Reductases and ω‐Transaminases for the Stereoselective Synthesis of Diastereomerically Enriched Amines. Issue 19 (10th August 2015) - Monti, Daniela; Forchin, Maria Chiara; Crotti, Michele; Parmeggiani, Fabio; Gatti, Francesco G.; Brenna, Elisabetta; Riva, Sergio
Abstract One‐pot sequential and cascade processes performed by employing ene‐reductases (ERs) together with ω‐transaminases (ω‐TAs) for the obtainment of diastereomerically enriched (R)‐ and (S)‐amine derivatives containing an additional stereocenter were investigated. By using either α‐ or β‐substituted unsaturated ketones as substrates and by coupling purified ERs belonging to the Old Yellow Enzyme (OYE) family with a panel of commercially available ω‐TAs, the desired products were obtained in up to >99 % conversion and >99 % de. The sequential reactions were performed in a one‐pot fashion with no need to adapt the reaction conditions to the reductive amination step or to purify the reaction intermediate. Moreover, high chemoselectivity of the tested ω‐TAs for the saturated ketones was shown in the cascade reactions.